Achados incidentais no rastreamento de câncer de pulmão: ensaio pictórico e lista de verificação sistemática - Penha, Diana; Pinto, Erique; Monaghan, Colin; Hochhegger, Bruno; Marchiori, Edson; Taborda-Barata, Luís; Irion, Klaus; Ravara, Sofia; Kauczor, Hans-Ulrich (Jornal Brasileiro de pneumologia, 2022)
Lung cancer screening (LCS) programs are increasing worldwide. Incidental findings (IFs) on LCS are defined as low-dose CT findings unrelated to the primary purpose of identifying lung cancer. Most IFs on LCS are benign and clinically insignificant but are being increasingly recognized, and some require urgent referral for further diagnostic workup. Other findings are expected and are known as smoking-related comorbidities, including COPD, cardiovascular disease, emphysema, and interstitial lung disease, and their diagnosis can have a significant impact on patient prognosis. The purpose of this pictorial essay is to illustrate the most common IFs on LCS, organized by organ. We will discuss the current literature on IFs on LCS, focusing on their prevalence, appropriate communication, and triggering of clinical pathway systems.
Gesehen am 25.05.2022